1985
DOI: 10.1159/000242100
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Metabolic Rate and Body Size in Fetal Life

Abstract: To define the O2 consumption rate (VO2) versus body mass relation during fetal growth, we compared fetal sheep VO2 at mid and late gestation. VO2 per kg wet weight was 37% higher at mid gestation. However, VO2 per kg dry weight was 2.5 times higher, and associated with a high viscera/body weight ratio. Fetal VO2 tends to grow proportionally to body mass because marked decreases in the relative growth of visceral organs and in the VO2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

1986
1986
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 8 publications
0
5
1
Order By: Relevance
“…The small babies tend to have slightly higher met abolic rates per kilogram body weight than normal ones, and their body temperatures also tend to be lower in a cool environment, suggesting that in the human the increased metabolic rate is not enough to offset the greater heat loss. In the fetus, heat loss does not occur from the surface of the body and consequently metabolic rate is related more closely to body weight, as demonstrated in the sheep by Bell et al [1985], At the tissue level the findings of the present study are in contrast to results ob served in older growing piglets. The activi ties of respiratory enzymes in the longissimus dorsi muscle from runts were in fact lower than in controls, whereas in older pigs it was the animals on the high energy intake which had the lower activities of respiratory enzyme [Dauncey et al, 1986], In the present study the muscle tissue of the heart and diaphragm revealed no differences in enzyme activity suggesting that essential tis sues had been spared during fetal undernu trition.…”
Section: Discussioncontrasting
confidence: 68%
“…The small babies tend to have slightly higher met abolic rates per kilogram body weight than normal ones, and their body temperatures also tend to be lower in a cool environment, suggesting that in the human the increased metabolic rate is not enough to offset the greater heat loss. In the fetus, heat loss does not occur from the surface of the body and consequently metabolic rate is related more closely to body weight, as demonstrated in the sheep by Bell et al [1985], At the tissue level the findings of the present study are in contrast to results ob served in older growing piglets. The activi ties of respiratory enzymes in the longissimus dorsi muscle from runts were in fact lower than in controls, whereas in older pigs it was the animals on the high energy intake which had the lower activities of respiratory enzyme [Dauncey et al, 1986], In the present study the muscle tissue of the heart and diaphragm revealed no differences in enzyme activity suggesting that essential tis sues had been spared during fetal undernu trition.…”
Section: Discussioncontrasting
confidence: 68%
“…Another prediction consequent upon the discrepancy between exponents for fetal oxygen consumption (c. 0.88, Hofman, 1983;Bell et al 1985) and placental diffusive conductance (c. 0.99, present study) is that oxygen partial pressure gradients across the placenta decline during gestation. In fact, analysis of gestational changes in intervillous oxygen tensions indicate a rise from 6-7 kPa to about 8 kPa between 12 and 16 weeks of gestation and then a gradual decline to roughly 6 kPa at term (Soothill et al 1986;Rodesch et al 1992;Jauniaux et al 2001).…”
Section: )mentioning
confidence: 54%
“…Human term fetuses in this study had a mass of about 3.5 kg. Using allometric equations for predicting neonatal oxygen intakes from birthweights (Hofman, 1983;Bell et al 1985), a 3.5-kg newborn is expected to consume oxygen at a rate of 27 cm 3 min −1 .…”
Section: Discussionmentioning
confidence: 99%
“…It is striking that it is 42% higher than the value of 360 /-tmol· min-I. kg-I reported for the near-term sheep (21). However, the near-term fetal guinea pig contains 76% water, less than the 83.3% of the fetal lamb of corresponding gestational age (1,22).…”
Section: Resultsmentioning
confidence: 71%